The genus Rhabdomastix Skuse in Australia (Diptera: Tipuloidea: Limoniidae) - Theischinger, Günther; Billingham, Zacariah D.; Martin, John; Growns, Ivor (Zootaxa, 2019)
The crane fly genus Rhabdomastix Skuse, 1890 is briefly introduced, the four species hitherto known from Australia are reviewed. The male of R. tonnoirana Alexander, 1934 and the female of R. wilsoniana Alexander, 1934 are described for the first time and R. minima Alexander, 1926 is considered as nomen dubium. A further eight Australian species are described as new, their affinities and distributions are discussed. They are R. borroloola sp. nov., R. dobrotworskyi sp. nov., R. dooragana sp. nov., R. hirsuta sp. nov., R. nivalis sp. nov., R. ponticulus sp. nov., R. collessiana sp. nov., R. rosae sp. nov.  A key to the males of Australian Rhabdomastix is presented.